Gaze-shift patterns during a jump with full turn in male gymnasts - Sato, Y.; Torii, S.; Sasaki, M.; Heinen, T. (Perceptual and Motor Skills, 2017)
When airborne, gymnasts skillfully control their movements to achieve a successful landing. Utilizing visual information from task-specific eye-body coordination patterns (i.e., visual spotting) is thought to be important for gymnasts in the performance of aerial skills. The purpose of this study was to assess the interplay of eye movements and body movements in an aerial skill with a rotation about the longitudinal axis, namely a straight jump with full turn. Participants were 10 skilled male gymnasts (age [M±SD], 23.90 ± 3.28 years) and 14 male nongymnasts (20.57 ± 2.90 years). Gaze behavior during each jump was determined by measuring and integrating eye and head movement data. Results revealed two distinct gaze-shift patterns: a single-step gaze-shift pattern and a multistep gaze-shift pattern. In both patterns, skilled gymnasts stabilized their gaze prior to takeoff and again prior to landing. Whichever pattern was used, gymnasts started to stabilize their gaze on average about 110 milliseconds before landing, which was earlier than nongymnasts. The results suggest that gymnasts use visual information obtained by a particular gaze behavior to generate the necessary amount of rotation and to perform a precise landing in aerial skills involving whole-body rotations. ABSTRACT FROM AUTHOR